Socialization of corner care in newborn babies as an efforts to prevent infections in the corner at PMB Ernita Pekanbaru - Risa Pitriani; Rika Andriyani (Peneliti Teknologi Teknik Indonesia, 2021)
The umbilical cord or in medical terms known as the umbilical funiculus is a lifeline for the fetus during the womb. Caring for the umbilical cord is also important to prevent neonatal tetanus, which can cause death. The body of a newborn baby is not strong enough to ward off infectious germs. Based on the results of the survey, it was found that mothers who had babies aged 0-7 days did the wrong umbilical cord care. Of the 5 pregnant women found, 2 of them still use spices (turmeric) to speed up the delivery of the umbilical cord. In PMB Ernita in the last 6 months has never done any counseling related to umbilical cord care. So it is necessary to carry out activities to overcome the problems found through the socialization of umbilical cord care for mothers. The target of this activity is to increase knowledge about proper umbilical cord care so that it can change the mother's behavior in caring for the newborn's umbilical cord. The results of this activity will be published in the community service journal of Muhammadiyah University of Riau. This activity was carried out in 2 stages: 1. Counseling was carried out on November 16, 2020, 2. The stage of coaching, monitoring and evaluation was carried out for 1 week with home visits from November 23 - 29 2020. The results of this activity were 1) Increased knowledge of mothers who have a baby about the correct care of the umbilical cord is seen from the ability of the baby's mother in answering the questions posed by the speaker, of the 10 questions given by the speaker can be answered by the baby's mother. 2) Increasing the skills of the baby's mother in properly caring for her own umbilical cord, so that it is possible for participants to apply these skills in daily life. This can be seen when the service team makes home visits. It is hoped that health workers in this case midwives can prepare postpartum mothers in caring for newborns, especially umbilical cord care starting from pregnancy.